2013
DOI: 10.1111/sji.12023
|View full text |Cite
|
Sign up to set email alerts
|

Mammal‐Derived Respiratory Lipocalin Allergens do not Exhibit Dendritic Cell‐Activating Capacity

Abstract: Most mammal-derived respiratory allergens belong to the lipocalin family of proteins. Determinants of their allergenic capacity are still unknown. Innate immune cells, in particular dendritic cells, have been shown to be involved in the allergenicity of some proteins. As recognition by dendritic cells is one of the few plausible mechanisms for the allergenicity of proteins, we wanted to investigate their role in the allergenicity of lipocalin allergens. Therefore, we first incubated human monocyte-derived dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In accordance with this conception, there are several reports indicating that in vitro T cell responses to an allergen do not correlate (or correlate very weakly) with the production of specific IgE in humans [23][25]. Therefore, poor T cell recognition, together with inefficient activation of the cells of innate immunity [76], also reported for several other allergens [77][79], appears as a likely immunological property of lipocalin allergens promoting their allergenicity since it is well documented that suboptimal T cell recognition of an antigen favors the development of Th2-type immune responses [43][53]. Nevertheless, good immunogenicity can be a characteristic for some other groups of allergens than lipocalins.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In accordance with this conception, there are several reports indicating that in vitro T cell responses to an allergen do not correlate (or correlate very weakly) with the production of specific IgE in humans [23][25]. Therefore, poor T cell recognition, together with inefficient activation of the cells of innate immunity [76], also reported for several other allergens [77][79], appears as a likely immunological property of lipocalin allergens promoting their allergenicity since it is well documented that suboptimal T cell recognition of an antigen favors the development of Th2-type immune responses [43][53]. Nevertheless, good immunogenicity can be a characteristic for some other groups of allergens than lipocalins.…”
Section: Discussionmentioning
confidence: 81%
“…In particular, Can f 1 appears to be only marginally more potent to induce T cell responses than TL. As lipocalin allergens have also been shown to be weakly stimulatory to the cells of innate immunity [76], they may present themselves inert to the human immune system. When a protein with such characteristics encounters human atopic, Th2-biased immune environment, its subtle antigenicity may turn the fine balance of immunity for the favor of Th2 development.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the data shown in these reports are not directly comparable to our study, some are still contradictory. Virtanen and colleagues found that mammalian lipocalin allergens do not exhibit DC-activating capacity and found no differences in the CD4 + T cell responses to the two homologous lipocalins 38,39 while Preston et al . 40 found immunomodulatory activity of hard tick-derived lipocalins and Roth-Walter et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lipocalins share a common tertiary structure consisting of a β-barrel enclosing an internal ligand binding sites, but have very low sequence homology [25]. They are extracellular proteins whose expression is confirmed in bacteria, protoctists, plants, arthropods and chordates [26].…”
Section: Discussionmentioning
confidence: 99%